The Effect Of Electronic Office On Employees’ Work Effectiveness At The Regional Office Of The National Land Agency Of Bengkulu Province - Wella Mustika; Harius Eko Saputra; Antonio Imanda (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of the electronic office system on employees’ work effectiveness at the Regional Office of the National Land Agency of Bengkulu Province. This research applied a quantitative method with a survey approach. A total of 53 respondents were selected using a simple random sampling technique. Data analysis involved the product moment correlation test, simple linear regression, validity and reliability tests, t-test, and coefficient of determination. The findings reveal that the electronic office system significantly influences employees’ work effectiveness. The correlation coefficient of 0.409 indicates a moderate relationship between the variables. The coefficient of determination (R²) of 16.8% shows that the electronic office variable contributes to 16.8% of the variance in work effectiveness. Furthermore, the t-value (3.204) exceeds the t-table value (2.006), meaning that the hypothesis is accepted. Thus, the use of the electronic office system has a positive and significant effect on improving employees’ work effectiveness at the Regional Office of BPN Bengkulu Province.